190k views
2 votes
Which is the value of this expression when a=-2 and b=-3

Which is the value of this expression when a=-2 and b=-3-example-1
User Gearhead
by
5.2k points

2 Answers

5 votes

Answer:

729/64

Explanation:

User Molloch
by
5.4k points
1 vote

Answer:


(729)/(64)

Explanation:

The given expression is


((3a^(-3)b^(2) )/(2a^(-1) b^(0) ) )^(2)

Where
a=-2 and
b=-3.

When we say "evaluate the expression" refers to replacing the given values in the expression. Then, we solve each power in the numerator and denominator. After that, we solve each product in the fraction. At the end, we apply the square power. As follows


((3a^(-3)b^(2) )/(2a^(-1) b^(0) ) )^(2)=((3(-2)^(-3)(-3)^(2) )/(2(-2)^(-1) (-3)^(0) ) )^(2)=((3((1)/(-8))(9))/(2((1)/(-2) (1))) )^(2) =((-(27)/(8) )/(-1) )^(2) =(27^(2) )/(8^(2) ) =(729)/(64)

User Nomoa
by
5.8k points